Influence of consumption of commercial hemp-based products on the detection of tetrahydrocanabinol in urine by immunochromatographic test strips - Šuić, Ana; Javorac, Dragana; Baralić, Katarina; Marić, Djurdjica; Antonijević Miljaković, Evica; Buha Djordjević, Aleksandra; Ćurčić, Marijana; Djordjević, Snežana; Djukić-Ćosić, Danijela; Antonijević, Biljana; Bulat, Zorica (Archives of Pharmacy, 2022)
According to the current regulations in Serbia, the cultivation and sale of hemp-based products (Cannabis sativa L.) containing up to 0.3% of substances from the group of tetrahydrocannabinol is allowed. ∆-9-tetrahydrocannabinol (THC) is responsible for the psychoactive effects and the development of cannabis addiction. A growing number of products based on parts or the whole cannabis plant are on free sale. Since cannabis is the most commonly used psychoactive substance, there is a greater need for quick and easy detection in the body. The Aim of this project was to examine the effect of commercial cannabis-based products consuption on urine THC detection by using immunochromatographic test strips. Eight healthy volunteers consumed commercially available hemp-based products (four tea products, two ground and two whole seeds products). The products were consumed according to the instructions given by the manufacturer, for three consecutive days, and on the fourth day the first morning urine was tested for the presence of THC using multicomponent One Step Rapid Test®-Ameritek® test strips. Urine samples from five subjects gave a negative test result, and three samples, from subjects who consumed hemp ground seeds and tea in bulk, gave a positive THC test. Further analysis of positive urine samples by the conformative method (HPLC-PDA) did not prove the presence of THC. Consumption of certain commercial cannabis-based products can lead to false-positive results in the detection of THC in urine by immunochromatographic test strips. Therefore, it is necessary to perform further analysis of urine by conformative methods.